Maternal nutritional awareness and iron deficiency anemia in children aged 6 months–2 years in a tertiary care hospital in Coimbatore, Tamil Nadu - Sheik, Shahana Parvin; Saidalikutty, Fouzeamol (Indian Journal of Child Health, 2022)
Objective: This study aims to analyze the risk factors and vital role of mothers in prevention of nutritional anemia in the early childhood. Methods: A hospital-based cross-sectional study done in Coimbatore for 2 years. Using a pre-tested structured validated tool, mothers of children aged 6 months–2 years were interviewed to collect information on factors contributing to anemia with special regard to maternal knowledge. Results: Anemia was more in the latter half of infancy (67.2%) with male predominance (60.5%). An affirmative association between increased cow’s milk intake and low hemoglobin was present (p=0.002). Employed and less educated mothers had more anemic children (p